1984
DOI: 10.1021/ma00134a037
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of nonaffine and inhomogeneous deformation of network chains in strained rubber-elastic networks by deuterium magnetic resonance

Abstract: The segmental orientation of uniaxially strained poly(l,4-butadiene) networks was probed by deuterium magnetic resonance over a wide range of extension ratios. The experiments were performed on homogeneously deuterated networks and on partially deuterated networks with short deuterated segments at network junctions. The analysis of the strain-dependent line shapes of the deuterium resonances is interpreted in terms of a nonaffine deformation mechanism by means of which short elastically effective chains are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 10 publications
(16 reference statements)
5
100
0
Order By: Relevance
“…Investigations on aqueous polyacrylic acid/polyvinyl alcohol gels [11,12], on polystyrene networks swollen in naphthalene [4] and on rubbers swollen in benzene [13][14][15][16][17][18] showed a freezing point depression in a network polymer depending on the cross-linking density v. The crystal dimension Dk is assumed to be equal to the distance between the junction points in the swollen state de. The investigation of the freezing process of suitable swelling agents [1] in a network polymer, depending on the time, opens the possibility, by analogy with anorganic-porous materials, to determine the distribution of Dk and hence the distribution of the distance between the junction points in the swelling equilibrium, which so far has been only accessible at increasing experimental expense [19][20][21][22][23][24] or not at all.…”
Section: At-z Tslo Asl (La) Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations on aqueous polyacrylic acid/polyvinyl alcohol gels [11,12], on polystyrene networks swollen in naphthalene [4] and on rubbers swollen in benzene [13][14][15][16][17][18] showed a freezing point depression in a network polymer depending on the cross-linking density v. The crystal dimension Dk is assumed to be equal to the distance between the junction points in the swollen state de. The investigation of the freezing process of suitable swelling agents [1] in a network polymer, depending on the time, opens the possibility, by analogy with anorganic-porous materials, to determine the distribution of Dk and hence the distribution of the distance between the junction points in the swelling equilibrium, which so far has been only accessible at increasing experimental expense [19][20][21][22][23][24] or not at all.…”
Section: At-z Tslo Asl (La) Lmentioning
confidence: 99%
“…A clear picture of the relationship between the absolute size of Dk, calculated from/iT, and the distance between the junction points can be obtained by comparison with absolutely measured distances between the junction points, which are measurable by small-angle X-ray scattering (SAXS) [23] and small-angle neutron scattering (SANS) [24,35], but only for networks with marked cross-links. For PDMS-network (Me --21,00 g mo1-1) swollen in benzene de~ Q1/3 = 8.4 nm [35] was measured.…”
Section: Crystal Size and Distance Between Junction Pointsmentioning
confidence: 99%
“…-An additional deviation from the behaviour of the homopolymers could arise from differences in the deformation mechanism of block copolymers. In the case of poly(butadiene) networks [14] it has been shown that the microscopic deformation ratio is smal- SBS-150-h at various strains; the samples were stretched at room temperature and cooled (10 K/min) to 150 K prior to heating ler than the macroscopic one. A similar explanation could be applied to the block copolymers and account for the convex curvature in Figure 10.…”
Section: B Theory Of Stress Induced Crystallizationmentioning
confidence: 99%
“…[5] THEORY By spectroscopic deuteron imaging for different sample In 2 H NMR spectroscopy, deuterated, unstretched elasto-orientations, the local quadrupole splitting can be determined mers exhibit a single line, because the quadrupole interac-for each sample orientation c, so that by Eq. [4] the local tions are averaged by fast, isotropic molecular motion of the stress tensors can measured. network chains.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to P 2 (cos C) Å 0 (4)], and with Eq. [4], one arrives at distribution of chain segments, the splitting can be expressed in the network coordinate frame (4)…”
Section: Introductionmentioning
confidence: 99%